2016
DOI: 10.1371/journal.pone.0161277
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Algorithm in the Management of Acute Febrile Abdomen in Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: BackgroundAcute febrile abdomen represents a diagnostic challenge in patients with autosomal dominant polycystic kidney disease (ADPKD). Although criteria have been proposed for cyst infection (CyI) and hemorrhage (CyH), there is a lack of comparative assessments. Furthermore, distinguishing cystic from non-cystic complications remains problematic.DesignADPKD patients presenting with abdominal pain and/or fever between 01/2005 and 06/2015 were retrospectively identified in a systematic computerized billing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
1
23
0
2
Order By: Relevance
“…Cyst infection is a very rare complication of childhood ADPKD. If suspected clinically or on ultrasonography imaging, experience in adults suggests that 18 F-FDG-PET/computed tomography (CT) is superior to contrast CT or MRI to confirm the diagnosis and localize the infected cyst, but this approach can produce false-negative results 143,144 . Treatment of cyst infection has a high failure rate and requires long-term use of antibiotics 145 .…”
Section: Urinary Tract and Cyst Infectionsmentioning
confidence: 99%
“…Cyst infection is a very rare complication of childhood ADPKD. If suspected clinically or on ultrasonography imaging, experience in adults suggests that 18 F-FDG-PET/computed tomography (CT) is superior to contrast CT or MRI to confirm the diagnosis and localize the infected cyst, but this approach can produce false-negative results 143,144 . Treatment of cyst infection has a high failure rate and requires long-term use of antibiotics 145 .…”
Section: Urinary Tract and Cyst Infectionsmentioning
confidence: 99%
“…Lantiga et al recently summarized diagnostic criteria for liver cyst infection: infection is « de inite » if con irmed by cyst content analysis showing bacteria or neutrophils, infection is « probable » if the four following criteria are concomitantly met: 3-day fever >38°C, liver tenderness, CRP plasma levels >50 mg/L and no CT evidence for cystic haemorrhage. Additional criteria are weight loss, recent instrumentation of biliary tract and increased white blood cell count [6].…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of cyst aspiration and subsequent microbiologic testing for previously mentioned reasons, a composite reference standard based on the criteria of Sallée et al (5,(10)(11)(12)(13) was used for cyst infection. According to these criteria (5,10-13), hepatic or renal cyst infection was (likely) considered to be present when a patient met all 5 of the following criteria: fever exceeding 38.5°C for more than Other clinical criteria and follow-up were used as reference standard for diagnosing cyst infection on 18 F-FDG PET/CT.…”
Section: Reference Standardmentioning
confidence: 99%
“…Previous studies reported 18 F-FDG PET/CT to be useful in ADPKD patients (Table 1) (5,(10)(11)(12)(13)(14)(15). However, because of few included patients or unclear reporting of diagnostic power in these studies, there is still no consensus on the widespread use of 18 F-FDG PET/CT in this setting.…”
mentioning
confidence: 99%